WORK-LIFE BALANCE'S IMPACT ON EMPLOYEE ENGAGEMENT WITH JOB CRAFTING AS MEDIATION VARIABLES IN HEALTH DEPARTMENT EMPLOYEES PADANG-PANJANG CITY - Tedi, Tedi Pratama; Mega asri zona (Human Resource Management Studies, 2023)
This study identifies and examines: (1) How work-life balance affects employee engagement among Padang Panjang City Health Office staff (2) How work-life balance affects job crafting in Padang Panjang City Health Office staff (3) How job designing affects employee engagement among Padang Panjang City Health Office staff (4) The impact of job crafting as a mediating variable on work life balance with employee engagement in Padang Panjang City Health Office staff. Research of this kind called causal research. The research's 150 participants are the human resources staff at the Padang Panjang City Health Office. In this investigation, clusters proportional random sampling was the method of sampling. utilizing a Likert scale in a questionnaire to collect data. the method of analysis used to SEM data using PLS 4 (Partial Least Square) software. : Data analysis for this study's conclusions reveals the following:. (1) The employees of Padang Panjang City Health Office are considerably and favorably influenced by work-life balance in terms of employee engagement (2) work-life balance has a positive and significant effect on job crafting for employees of the Padang Panjang City Health Office (3) Employees of the Padang Panjang City Health Office report that job crafting has a major impact and helps employee engagement. (4) For employees of the Padang Panjang City Health Office, job crafting mediates the work-life balance relationship with employee engagement.